Energy analysis of an inerter‐enhanced floating floor structure (In‐FFS) under seismic loads. (26th July 2022) - Ma, Haomin; Cheng, Zhibao; Jia, Gaofeng; Shi, Zhifei
Abstract: To improve the seismic responses of the traditional floating floor structure (FFS), an inerter‐enhanced FFS, namely the In‐FFS, was recently proposed by the authors. The multifold improvements offered by the In‐FFS compared to the FFS have been investigated based on the seismic responses analysis. In this work, the superior performances of the In‐FFS are investigated and demonstrated based on the energy analysis method. It is found that, thanks to the dynamic equivalent mass effect of the inerter, the input energy of the entire system under seismic inputs is suppressed. Compared with the conventional frame structure (FS), the maximum mechanical energy of the primary structure is reduced by around 75% and 80% for the FFS and In‐FFS, respectively. As a result, dynamic responses of the primary structure are greatly mitigated. More importantly, the inerter attachment can effectively suppress the maximum kinetic energy of the FFSs (e.g., by more than 50%). The relative displacements between the floating floor slabs and the primary structure are reduced by more than a half. The energy dissipation capacity of the inerter attachment is much better (about two times) than that of the traditional isolator with the same damper. Compared to its two degenerated models, the proposed inerter attachment can suppress both the maximum mechanical energy of the primary structure and the maximum kinetic energy of the floating floor slab at the same time. Overall, the proposed In‐FFS outperforms the traditional FFS. It enhances the multifold advantages of the FFS (i.e., the small interstory drift responses of the primary structure and the limited absolute acceleration response of the floating floor slab); meanwhile, it also eliminates a main disadvantage of the FFS (i.e., the large relative displacement between the floated floor slabs and the primary structure).